Was the mandal commission right? Living standard differences between backward classes and other social groups in India - Ira N. Gang; Kunal Sen; Myeong-Su Yun (Institute for the Study of Labor (IZA), 2008)
Affirmative action has been at the heart of public policies towards the socially disadvantaged in India. Compensatory discrimination policies which have been adopted for the Scheduled Castes (SC) and Scheduled Tribes (ST) since independence were recommended for Other Backward Classes (OBC) by the Mandal Commission established by the Indian government in 1979. We examine why OBC have lower living standards, as measured by per capita household consumption expenditures, relative to the mainstream population, and whether these reasons are similar to those observed for SC and ST. We find that while the causes of the living standard gap for the OBC are broadly similar to those for the SC and ST, the role of educational attainment in explaining the gap is higher in importance for the OBC.
urn:nbn:de:101:1-20080421103
Keywords: I32; 300; Living standards; caste; reservation policy; decomposition; Lebensstandard; Einkommensverteilung; Soziale Schicht; Verbraucherausgaben; Bildungsabschluss; Sozialpolitik; Indien